A discourse analysis on prefaces In english and vietnamese - Phan Thảo My (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Based on the theories of Discourse Analysis, this study makes an investigation into the English Prefaces (EPs) and Vietnamese Prefaces (VPs) in an attempt to discover some typical discourse features and then find out the similarities and differences between EPs and VPs in term of the thematisation, moves, lexical features, syntactic features and cohesive devices to suggest some implications for teaching English to Vietnamese learners. The findings obtained from the thematisation show that EPs and VPs share the similar thematisation. However, the struture in EPs tends to be: (Problem Setting)- Sources of Inspiration-Research Problem/ Purpose- Audiences-Book Description- Conclusion or Implications whereas the structure in VPs is usually as follows: Problem setting- Purpose- (Overview of the Content)- Conclusion or Implications. With regard to syntactic structures, while the passive voice is more common in EPs, cleft sentences are more popular in VPs. To draw and create attention from the readers, speech acts are considered an effective tool, of which directives take the dominant role. With regard to cohesion, the results show that reference was most frequently used, followed by lexical repetition, conjunction, substitution and ellipsis, Hopefully, the results of the study can be somewhat beneficial for the teaching and learning of English. This study may also be helpful for those who want to produce.